1993
DOI: 10.1111/j.1432-1033.1993.tb17786.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residues involved in the catalytic site of human erythrocyte bisphosphoglycerate mutase

Abstract: Human bisphosphoglycerate mutase (Grip, mutase) is a trifunctional enzyme which synthesizes and degrades Grip, in red cells. Among the amino acid residues involved in its active site there are two conserved histidine residues, HislO which is phosphorylated during the catalytic process and His187 for which only speculative data have been made about the potential role during the reactions. Another amino acid residue, Arg89, had not been described as part of this active site but we have recently shown that a natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…As previously reported (24), the R89K mutated protein presents increased Michaelis constants for monophosphoglycerates, whereas the 2,3-DPG one is not affected. Our present results demonstrated that its affinity for 2-phosphoglycolate was also unchanged, indicating that Arg 89 is only involved, directly or indirectly, in the monophosphoglycerate-binding sites.…”
Section: -Phosphoglycolate-binding Site In Bisphosphoglycerate Mutasesupporting
confidence: 60%
See 4 more Smart Citations
“…As previously reported (24), the R89K mutated protein presents increased Michaelis constants for monophosphoglycerates, whereas the 2,3-DPG one is not affected. Our present results demonstrated that its affinity for 2-phosphoglycolate was also unchanged, indicating that Arg 89 is only involved, directly or indirectly, in the monophosphoglycerate-binding sites.…”
Section: -Phosphoglycolate-binding Site In Bisphosphoglycerate Mutasesupporting
confidence: 60%
“…Arg 89 Is Specifically Involved in the Monophosphoglyceratebinding Site-Previous results obtained in our laboratory strongly suggested that the Arg 89 residue of human BPGM is specifically involved in the 3-PG-binding site (24,27). We completed the functional studies on the R89K mutant by investigating the ion-stimulated phosphatase activity and measuring the affinity constant for 2-phosphoglycolate.…”
Section: -Phosphoglycolate-binding Site In Bisphosphoglycerate Mutasementioning
confidence: 98%
See 3 more Smart Citations